2018
DOI: 10.3164/jcbn.17-54
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect of <i>Dioscorea japonica</i> on squamous cell carcinoma of mouse skin involving down-regulation of prostaglandin E<sub>2</sub> synthetic pathway

Abstract: Hyperproduced prostaglandin E2 by cyclooxygenase-2 and microsomal prostaglandin E synthase-1 evokes several pathophysiological responses such as inflammation and carcinogenesis. Our recent study demonstrated that Dioscorea japonica extract suppressed the expression of cyclooxygenase-2 and microsomal prostaglandin E synthase-1 and induced apoptosis in lung carcinoma A549 cells. In the present study, we investigated the effects of Dioscorea japonica on squamous cell carcinoma of mouse skin. Dioscorea japonica fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…We have been exploring food functionality for the prevention of chronic inflammation by targeting the synthetic pathway of proinflammatory lipid mediators, such as prostaglandin (PG) E2 and leukotrienes, derived from ω-6 arachidonic acid. In our previous study, we have demonstrated that Dioscorea japonica, a wild yam, suppresses the activity of cyclooxygenase-2 (COX-2) and microsomal prostaglandin E (PGE) synthase-1, which are key enzymes in the production of proinflammatory PGE2, and has anti-inflammation and anti-carcinogenesis [12,13]. Recently, it is reported that diosgenin, a functional ingredient of Dioscorea japonica, downregulates COX-2 expression selectively in macrophages via glucocorticoid receptor and improves LPS-induced liver inflammation [14].…”
Section: Introductionmentioning
confidence: 99%
“…We have been exploring food functionality for the prevention of chronic inflammation by targeting the synthetic pathway of proinflammatory lipid mediators, such as prostaglandin (PG) E2 and leukotrienes, derived from ω-6 arachidonic acid. In our previous study, we have demonstrated that Dioscorea japonica, a wild yam, suppresses the activity of cyclooxygenase-2 (COX-2) and microsomal prostaglandin E (PGE) synthase-1, which are key enzymes in the production of proinflammatory PGE2, and has anti-inflammation and anti-carcinogenesis [12,13]. Recently, it is reported that diosgenin, a functional ingredient of Dioscorea japonica, downregulates COX-2 expression selectively in macrophages via glucocorticoid receptor and improves LPS-induced liver inflammation [14].…”
Section: Introductionmentioning
confidence: 99%
“…Yam is also known to have digestive functions in the stomach and intestines, as well as immune-regulatory and antiaging effects. In modern pharmacology, the yam has been studied for its effects on asthma [ 7 ], cancer [ 8 , 9 , 10 ], diabetes [ 11 , 12 ], and liver damage [ 13 ], as well as its anti-oxidation, anti-inflammation, and anti-aging effects [ 14 , 15 ]. The yam contains various compounds such as dioscin [ 16 ], steroidal saponins [ 16 , 17 ], saponins, gallic acid, vanillic acid [ 14 ], allatoin [ 12 ], and protodioscin [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Allantoin, a diureide of glyoxylic acid, is an active and abundant component of yam [ 10 , 12 , 20 ]. In vivo studies have shown allantoin to have anti-asthmatic [ 20 ], antidiabetic [ 12 , 21 ] and antihypertensive [ 22 ] activities, as well as memory-enhancing effects in Alzheimer’s disease [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yam contains various compounds such as dioscin [15], steroidal saponins [15,16], saponins, gallic acid, vanillic acid [13], allatoin [11], and protodioscin [17]. Allantoin, a diureide of glyoxylic acid, is an active and abundant component of yam [9,11,18]. In vivo studies have shown allantoin to have anti-asthmatic [18], anti-diabetic [11,19] and anti-hypertensive [20] activities, as well as memory-enhancing effects in Alzheimer's disease [21].…”
Section: Introductionmentioning
confidence: 99%
“…In modern pharmacology, yam has been studied for its effects on asthma [6], cancer [7][8][9], diabetes [10,11], and liver damage [12], as well as its antioxidation, antiinflammation, and antiaging effects [13,14]. Yam contains various compounds such as dioscin [15], steroidal saponins [15,16], saponins, gallic acid, vanillic acid [13], allatoin [11], and protodioscin [17].…”
Section: Introductionmentioning
confidence: 99%